Effect of outdoor noise and façade sound insulation on indoor acoustic environment of Italian schools. (November 2017) - Secchi, Simone; Astolfi, Arianna; Calosso, Giulia; Casini, David; Cellai, Gianfranco; Scamoni, Fabio; Scrosati, Chiara; Shtrepi, Louena
Highlights: Façade sound insulation and reverberation time of about 100 classrooms were analysed. Data collected were compared to the ones of the Italian school building stock. Façade sound insulation measured before and after the acoustic treatments of façades. For each classroom the STI was calculated in occupied and in unoccupied conditions. The effect of short duration noise events was evaluated in each classroom. Acoustic treatment of façades was effective respect to short duration noise events. Abstract: The paper deals with the effect of outdoor noise mainly due to traffic and façade sound insulation on indoor noise level and speech intelligibility in classrooms. Results refer to the complete building stock of the Italian school buildings based on a census of the Italian Ministry of Education. The selected school sample consists of more than one hundred Italian schools of all levels (from nursery to upper secondary school) located in three Italian regions, built in different time periods and with different building techniques. The selected sample is representative of typical Italian schools. The façade sound insulation and the reverberation time of each school have been measured. The average outdoor noise level of about half the investigated schools has been measured and, for each school, the age of the building and the main characteristics of the façade have been listed (kind of glass, kind of ventilation, windows size, etc.). Based on these data, the correlations between both the main characteristics of the façades and the year of construction and the façade sound insulation have been investigated. Moreover, the influence of the noise coming from outdoor on the indoor noise level, speech intelligibility and speech to noise ratio have been analysed with reference to the situations both before and after the works carried out to improve the acoustic performances of façades. Results show that the indoor sound pressure level due to traffic noise is considerably reduced after the improvement of the façade acoustic insulation, while further treatments to indoor surfaces should be necessary to reduce internal reverberation time and to improve speech intelligibility.